POSTCOLONIALISM AND ITS IMPACT WITH SPECIAL REFERENCE TO SELECTED NOVELS OF PAUL SCOTT AND ROHINTON MISTRY - Khalid Altaf Sheikh; Dr. Harbhajan Kaur Khanooja (International Journal of Innovations in Engineering Research and Technology, 2023)
The aftermath of Colonialism or the effects of Imperialism on Africa, Asia, America, and other colonized countriesis very disastrous. To studyPostcolonialism, needs understanding of “post” in this concept. It means a reaction from the colonized and aiming at ending colonial tendencies.Postcolonialism is a dynamic field of literary study that focuses on the history of colonialism and native responses to colonial policies and life after colonialism, which brought a sharp change in the life and its conditions. The literature and culture of the former European colonies and their struggle after the end of colonialismdisplay how Said, African writers and Asian revolutionaries put forward their ideologies to counter the above structured concept.Postcolonialism examines the philosophical, moral, and political issues surrounding alienation, displacement, gender, country of residence, race, and ethnicity. It also aims at developing the national identity in the wake of colonial rule. In 1914, three fourth of the entire world was colonized by a minority of Europeancolonial powers. After the Second World War, almost all the colonized countriesattained independence, it was possible because of this concept, which has taken birth after 1940s. Postcolonialism was actually reawakening to revolutionary ideas that pushed back the power and gave consciousness to powerless legally. The themes and aspects of this concept are in abundance in the novels of Paul Scott and Rohinton Mistry. The researcher has tried to discuss, analyze and explain this idea and its impact in the novels of Scott and Mistry.